Pairing Voluntary Movement and Muscle-Located Electrical Stimulation Increases Cortical Excitability - Jochumsen, Mads; Niazi, Imran K.; Signal, Nada; Nedergaard, Rasmus W.; Holt, Kelly; Haavik, Heidi; Taylor, Denise (Frontiers in Human Neuroscience, 2016)
Learning new motor skills has been correlated with increased cortical excitability. In this study, different location of electrical stimulation (ES), nerve, or muscle, was paired with voluntary movement to investigate if ES paired with voluntary movement (a) would increase the excitability of cortical projections to tibialis anterior and (b) if stimulation location mattered. Cortical excitability changes were quantified using motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS) at varying intensities during four conditions. Twelve healthy subjects performed 50 dorsiflexions at the ankle during nerve or muscle ES at motor threshold (MTh). ES alone was delivered 50 times and the movement was performed 50 times. A significant increase in the excitability from pre- to post-intervention (P = 0.0061) and pre- to 30 min post-intervention (P = 0.017) measurements was observed when voluntary movement was paired with muscle ES located at tibialis anterior. An increase of 50 ± 57 and 28 ± 54% in the maximum MEPs was obtained for voluntary movement paired with muscle-located and nerve-located ES, respectively. The maximum MEPs for voluntary movement alone and muscle-located ES alone were −5 ± 28 and 2 ± 42%, respectively. Pairing voluntary movement with muscle-located ES increases excitability of corticospinal projections of tibialis anterior in healthy participants. This finding suggests that active participation during muscle-located ES protocols increases cortical excitability to a greater extent than stimulation alone. The next stage of this research is to investigate the effect in people with stroke. The results may have implications for motor recovery in patients with motor impairments following neurological injury.